A sexualidade após a lesão medular: análise de uma narrativa biográfica - Maia, Ana Cláudia Bortolozzi [UNESP] (2012)
Sexuality After Spinal Cord Injury: An Analysis of Biographical Narrative This descriptive qualitative study investigated sexuality issues by applying content analysis to an autobiographical narrative of a young woman with acquired spinal cord injury. The categories analyzed in the results were the following: (1) Everyday changes arising from becoming disabled, (2) Recognition of the identity of disabled person and (3) Emotional and sexual manifestations after the disability. Spinal cord injury can directly affect the sex life, but does not preclude the expression of sexuality. The perception of an erotic and desirable body was positively related to the family’s emotional support and to self-esteem. The narrative makes clear that sexuality is an important aspect of the restructuring of life after spinal cord injury and, therefore, sexual counseling should occur in the rehabilitation of the disabled person.